2019
DOI: 10.1002/mrm.28092
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional simultaneous brain T1, T2, and ADC mapping with MR Multitasking

Abstract: Purpose To develop a simultaneous T1, T2, and ADC mapping method that provides co‐registered, distortion‐free images and enables multiparametric quantification of 3D brain coverage in a clinically feasible scan time with the MR Multitasking framework. Methods The T1/T2/diffusion weighting was generated by a series of T2 preparations and diffusion preparations. The underlying multidimensional image containing 3 spatial dimensions, 1 T1 weighting dimension, 1 T2‐preparation duration dimension, 1 b‐value dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 65 publications
(154 reference statements)
0
58
0
Order By: Relevance
“…In addition, it has been shown that IR-TSE could lead to T1 underestimation in the brain compared to the traditional "gold standard" IR-SE. 28 Second, T2-preparations might lead to T2 underestimation due to B1 inhomogeneities, 33,69 while ME-SE was likely to cause T2 overestimation due to stimulated echo contamination. 70 Last, reference T1ρ mapping was subject to T1 contamination during the FLASH readouts despite the implementation of two-shot acquisition to allow fewer phase encoding lines per shot, which could also be the reason of blurriness in reference T1ρ maps but could be improved in future works by either implementing centric readout mode in both phase and partition encoding directions or using more shots at the expense of a longer scan time.…”
Section: Healthy Control Measurements (N = 14)mentioning
confidence: 99%
“…In addition, it has been shown that IR-TSE could lead to T1 underestimation in the brain compared to the traditional "gold standard" IR-SE. 28 Second, T2-preparations might lead to T2 underestimation due to B1 inhomogeneities, 33,69 while ME-SE was likely to cause T2 overestimation due to stimulated echo contamination. 70 Last, reference T1ρ mapping was subject to T1 contamination during the FLASH readouts despite the implementation of two-shot acquisition to allow fewer phase encoding lines per shot, which could also be the reason of blurriness in reference T1ρ maps but could be improved in future works by either implementing centric readout mode in both phase and partition encoding directions or using more shots at the expense of a longer scan time.…”
Section: Healthy Control Measurements (N = 14)mentioning
confidence: 99%
“…Currently, there are various low‐rank strategies available for reconstruction of the multidimensional arrays, either implicitly or explicitly 21,25‐29 . Magnetic resonance multitasking, based on the description of previous works, 21‐22,30,31 uses a mixed strategy that reconstructs the image tensor by directly recovering each of its factor matrices. Basically, in this work, image reconstruction can be divided into five steps:…”
Section: Methodsmentioning
confidence: 99%
“… Generate ungated images, which are reconstructed using explicit low‐rank matrix imaging with only one time dimension representing elapsed time, 21,22 for image‐based cardiac phase and respiratory position identification by means of a modified T 1 recovery–aware k ‐means clustering approach, 21 placing the corresponding images into 14 cardiac bins and 6 respiratory bins. Predetermine the temporal basis functions in ZtT1 (along the inversion‐recovery dimension) from a training dictionary of inversion‐recovery signals with different T 1 , T 2 , and B 1 inhomogeneity values, which is generated according to the Bloch equations ahead of time 21,31 Apply small‐scale low‐rank tensor completion to recover missing elements from a frequently sampled subset of k‐space (“auxiliary data”), which will be undersampled because it is impossible to acquire every combination of cardiac phase, respiratory phase, and inversion‐recovery time point: trueD^aux=argfalseminscriptDauxrangeZtT1∥∥daux-normalΩ)(scriptDaux22+λfalse∑n=14∥∥boldDaux,n,where daux is the collected auxiliary data; Ω· represents the undersampling pattern of the auxiliary data set; Daux,)(n denotes the mode‐n flattening of the completed auxiliary tensor; and · is the nuclear norm that promotes low‐rankness of each unfolded matrix.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations